2017
DOI: 10.4172/1989-8436.100051
|View full text |Cite
|
Sign up to set email alerts
|

Preventative and Curative Effect of Moringa oleifera Aqueous Extract to Ensure Safe Natural Antimicrobials Targeting Foodborne Pathogens

Abstract: The interest in biopreservation of food has prompted the quest for new natural antimicrobial compounds from different origins including plants. Medicinal plants are moving from fringe to mainstream use with a greater number of people seeking for remedies and health approaches from side effects caused by synthetic chemicals. This has aggravated the search for antimicrobials from plants sources. In this study, aqueous extract of Moringa oleifera was screened for antimicrobial activity against five foodborne bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This is often the case with events which have natural causes without agency but are of great social significance. For example, COVID-19 (Van Bavel et al, 2020), the Zika virus (Kadri & Trapp-Petty, 2016;Klofstad et al, 2019), Ebola virus (Falade & Coultas, 2017;Abramowitz et al, 2017;Coltart et al, 2017) and the Bubonic plague (Alcabes 2009;Brotherton, 2015) all have associated conspiracy theories which explain pandemics as the result of the actions of intentional agents rather than as natural occurrences. Further, studies have found a positive correlation between the tendency to attribute agency to inanimate objects and belief in a range of conspiracy theories (Douglas et al, 2016;Imhoff & Bruder, 2014).…”
Section: Content Dependent Biasesmentioning
confidence: 99%
“…This is often the case with events which have natural causes without agency but are of great social significance. For example, COVID-19 (Van Bavel et al, 2020), the Zika virus (Kadri & Trapp-Petty, 2016;Klofstad et al, 2019), Ebola virus (Falade & Coultas, 2017;Abramowitz et al, 2017;Coltart et al, 2017) and the Bubonic plague (Alcabes 2009;Brotherton, 2015) all have associated conspiracy theories which explain pandemics as the result of the actions of intentional agents rather than as natural occurrences. Further, studies have found a positive correlation between the tendency to attribute agency to inanimate objects and belief in a range of conspiracy theories (Douglas et al, 2016;Imhoff & Bruder, 2014).…”
Section: Content Dependent Biasesmentioning
confidence: 99%